Preservative Treatment of Keora (Sonneratia Apetala) Poles by Full Cell Method of Wood Preservation with CCA Preservative (Bangladesh Journal of Scientific and Industrial Research, 2012)
Keora (Sonneratia apetala Buch. Ham.) poles which contain mostly sapwood (more that 61%) and are readily susceptible to wood destroying agents were used in the study. Keora poles were treated with 5.5% CCA-C type preservative by full cell method of wood preservation for the period of 2, 3, 4 and 5 hours with the treating pressure of 200 psi (1,379 kPa). The maximum penetration was 4.36 cm for 5 hours treating duration. Retention and penetration increased with the increase of treating duration. The total retentions of CCA preservative were 9.15 kg m-3 for 2 hours, 12.72 kg m-3 for 3 hours, 16.35 kg m-3 for 4 hours and 18.31 kg m-3 for 5 hours treating duration for sapwood dominated keora poles. Significant variation in penetration and retention was found in the statistical analysis for different treating durations. Key words: CCA-C preservative; Full-cell method; Penetration; Retention; Sonneratia apetala DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9585 BJSIR 2011; 46(4): 425-428